Repair and Maintenance of Main Engine Cooling System on Fishing Vessels - Ziliwu, Boby Wisely; Situmorang, Agustunus Jhonri; Rambung, Richard Antonius (Jurnal Perikanan dan Kelautan, 2021)
Diesel engine is one type of piston motor fuel, whose fuel combustion occurs due to high air pressure in the combustion chamber. The combustion process diesel engine generates heat energy and raises the high pressure in the cylinder, the pressure is comverted to mechanical energy on the crankshaft. Then the cooling system is needed on the main engine. The cooling system is one system that functions to maintain the engine temperature at a certain temperature in accordance with the design specified so that the diesel engine can operate sustainably. This research work aims to find out how to work the ship’s cooling system, to find out how to maintain the ship’s cooling system, to find out the interference that occurs in the cooling system and to make repairs. The working of the cooling system at KM Sumber Fortuna use a cooling system indirectly / closed by using a heat excanger as a place to heat the heat excanger media by circulating fresh water to the entire machine to remove heat arising from combustion and friction in the engine. The method of maintenance is carried out with the duty service for 4 hours, the service carried ou is to check all the engine components in KM Sumber fortuna. While the damage occurred in the seawater suction pipe which had leaked in the pipe binder and replaced the leaked pipe by cutting the new pipe or hose and clamping the pipe / hose on the suction side of the heat exchanger.